Ripening physiology of five loquat (Eriobotrya japonica Lindl.) cultivars - Amorós A.; Zapata P.; Pretel M.T.; Botella M.A.; Almansa M.S.; Serrano M. (First international symposium on loquat, 2003)
The physiological changes related to ripening, such as colour, texture and sugar and organic acid levels and their relation with the plant hormone ethylene were studied in five cultivars of loquat. The five loquat cultivars showed a peak of ethylene production and an increase in 1-aminocyclopropane-1-carboxylic acid associated to the ripening changes in the above-mentioned parameters, although they started when loquat fruits were in an early phase of development when they had reached 60-70 percent of its final size.
1. International Symposium on Loquat, 2002/04/11-13, Valencia (Spain)